APPLICATION OF CRM METHODS FOR SALES SYSTEMS SHOES AND SANDAL PRODUCTS AT KOAKI STORE - Yuni Kartika Panjaitan; Nuriadi Manurung; Tika Christy (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: Koaki Store is a company engaged in the sale of various women's shoes and sandals that do not yet have the media to sell and promote the products they sell so that customers cannot know if there are new products or promo package products, unless the customer comes directly to the Koaki Store . As for the ordering process, customers must come directly to the store to buy products, this causes ineffective time utilization and inefficient costs incurred by customers who are far from the Koaki Store location, whereas if the order is made by telephone, customers cannot see directly . information about the products offered. In connection with this, a website-based application is needed at the Koaki Store that combines sub-systems including a sales system, recording order data, recording sales data, recording customer data online which becomes a unified system that is expected to be used to improve product sales services. The application of the CRM method is expected to be able to make customers loyal to the company so that the relationship that occurs is not only a relationship between sellers and buyers, but rather leads to a partner relationship. The goal to be achieved in this research is to facilitate the Koaki Store in providing online promotions in order to get new customers. Keywords : Customer Relationship Management; Customer Service; Sales Increase Abstrak: Koaki Store merupakan perusahaan yang bergerak di bidang penjualan aneka sepatu dan sandal wanita yang belum memiliki media untuk menjual dan mempromosikan produk yang mereka jual sehingga pelanggan tidak dapat mengetahui jika ada produk baru atau produk paket promo, kecuali pelanggan datang langsung ke Toko Koaki. Sedangkan untuk proses pemesanan, pelanggan harus datang langsung ke toko untuk membeli produk, hal ini menyebabkan tidak efektifnya pemanfaatan waktu dan tidak efisiennya biaya yang dikeluarkan oleh pelanggan yang jauh dari lokasi Toko Koaki, sedangkan jika pemesanan dilakukan melalui telepon, pelanggan tidak dapat melihat langsung . informasi tentang produk yang ditawarkan. Sehubungan dengan hal tersebut maka diperlukan suatu aplikasi berbasis website pada Toko Koaki yang menggabungkan sub sistem diantaranya sistem penjualan, pencatatan data pesanan, pencatatan data penjualan, pencatatan data pelanggan secara online yang menjadi satu kesatuan sistem yang diharapkan dapat digunakan untuk meningkatkan pelayanan penjualan produk. Penerapan metode CRM diharapkan mampu membuat pelanggan menjadi loyal kepada perusahaan sehingga hubungan yang terjadi tidak hanya hubungan antara penjual dan pembeli, melainkan lebih mengarah pada hubungan mitra. Tujuan yang ingin dicapai dalam penelitian ini adalah untuk mempermudah Toko Koaki dalam memberikan promosi secara online guna mendapatkan pelanggan baru. Kata Kunci : Customer Relationship Management, Layanan Pelanggan; Peningkatan Penjualan